Diversity and composition of vegetation and soil seed banks after sand dune restoration by oil mulching and plantations - Banafsheh Jalilian; Noredin Rostami; Mehdi Heydari; Mehrdad Kohzadian; Orsolya Valkó; Reza Omidipour (Scientific Reports)
Abstract Soil seed bank (SSB) is valuable reserves of seeds hidden in the soil and are especially important for the preservation and establishment of vegetation under adverse environmental conditions. However, there is a lack of knowledge on the effects of restoration measures on SSB, especially in arid ecosystems. Here, we assess the impacts of oil mulching (1 and 3 years after mulching) and plantations (15-year-old) on the diversity and composition of SSB and aboveground vegetation (AGV) in comparison with those in non-restored areas (i.e., control). Based on the results, species richness was poor in the studied area (36 species belonging to 16 families), with a lower contribution of SSB than of AGV (11 and 34 species, respectively). The largest number of exclusive species was observed in the planted treatment for both SSB and AGV (4 and 5 species, respectively), while the lowest was found in the 1-yr mulching treatment. The mean comparison of the diversity indices revealed that the highest values occurred in the plantation and 3-yr-mulching plots. The seed density in the plantation area was significantly greater (4145 ± 694 seeds/m2) than that in the other areas (3-yr-mulching > 1-yr-mulching > control treatments (145 ± 53, 65 ± 28, and 43 ± 22, respectively). The results of the DCA showed that the plantation treatment was completely separated from the other treatments in terms of the plant composition of the AGV, and the treatment closest to that area was 3-yr mulching, which indicates the positive effect of time since mulching on plant composition. The results of this study suggest that there is a trade-off between the short-term and medium-term effects of oil mulching, such that in the early years, oil mulching has a negative effect on the AGV and SSB, but its positive effects increase with time since mulching. It can be concluded that mulching, along with afforestation, creates a favorable microclimate and improves the diversity and composition of AGV and SSB.